9514 1404 393
Answer:
a) correct
b) needs parentheses: -1, (1±i√2)/3
Explanation:
a) You can factor by grouping:
(x³ -2x²) -(5x -10) = x²(x -2) -5(x -2) = (x² -5)(x -2)
Roots are ±√5, 2.
__
b) The sum of odd-degree coefficients is equal to the sum of even-degree coefficients (3-1 = 1+1), so one root is x=-1. Factoring out that leaves the quadratic factor ...
3x³ +x² -x +1 = (x +1)(3x² -2x +1)
The quadratic formula can be used on the quadratic factor to find its roots:
x = (-(-2) ±√((-2)²-4(3)(1)))/(2(3)) = (2 ±√-8)/6 = (1 ±√-2)/3
Roots are -1, (1 ±i√2)/3.